1983
DOI: 10.1073/pnas.80.21.6566
|View full text |Cite
|
Sign up to set email alerts
|

Avian carcinoma virus MH2 contains a transformation-specific sequence, mht, and shares the myc sequence with MC29, CMII, and OK10 viruses.

Abstract: Avian carcinoma virus MH2 has been grouped together with MC29, CMII, and OK10, because all of these viruses share a transformation-specific sequence termed myc. A 5.2-kilobase (kb) DNA provirus of MH2 has been molecularly cloned. The complete genetic structure of MH2 is 5'-delta gag(1.9-kb)-mht(1.2-kb)-myc(1.3-kb)-delta env(?) and noncoding c-region (0.2-kb)-3'. delta gag, delta env, and c are genetic elements shared with nondefective retroviruses, whereas mht is a unique, possibly MH2 transformation-specific,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…The transduction of more than one cellular gene into a single retrovirus is a relatively common event, in contrast to the previous belief: transduction of c-erb-A and c-erb-B gave rise to two strains of AEV, ES4 and R, isolated independently in the past (8), and both the MH-2 (11,12) and E26 (14, 16) a 8 9 10 11 12 13 14 15 16 17 18 19 20 (Fig. 1).…”
mentioning
confidence: 43%
See 1 more Smart Citation
“…The transduction of more than one cellular gene into a single retrovirus is a relatively common event, in contrast to the previous belief: transduction of c-erb-A and c-erb-B gave rise to two strains of AEV, ES4 and R, isolated independently in the past (8), and both the MH-2 (11,12) and E26 (14, 16) a 8 9 10 11 12 13 14 15 16 17 18 19 20 (Fig. 1).…”
mentioning
confidence: 43%
“…It has been suggested that these discrepancies arise from the fact that the MSB-1 cell line generally used for fractionation of chicken chromosomes (15,17) Bishop, unpublished data). It therefore appears safe to conclude that in chickens, as in other species (4), cellular oncogenes are dispersed among multiple chromosomes and that on several occasions two of these dispersed genes, c-erb-A and c-erb-B (29), c-myc and c-mil (also termed c-mht) (11,12), or c-mvb and c-ets (14,16), have been transduced into the genome of a single retrovirus.…”
mentioning
confidence: 99%
“…However, three oncogenic retroviruses contain two genes with oncogenic potential, namely the avian carcinoma viruses MH2 (2-5) and OK10 (6, 7) and avian erythroblastosis virus (AEV) (8,9). The 5.5-kilobase (kb) RNA genome of MH2 (10) has the genetic structure Agag-mht-myc (2)(3)(4)(5). One of the two genes with potential transforming function encoded by MH2 is a 3-kb Agag-mht gene, defined by a p100 protein product (11).…”
mentioning
confidence: 99%
“…Avian leukosis virus-induced bursal lymphomas were first reported by Ellerman and Bang (1908). Subsequently, a series of avian retroviruses, including MH2, OK10, MH29, and CMII (Duesberg and Vogt 1979;Bister and Duesberg 1980), were isolated and found to contain MYC sequences (Chiswell et al 1981;Bunte et al 1983;Hann et al 1983;Kan et al 1983; Thompson et al 1987). The name MYC originated from "myelocytomatosis," which consists of avian leukosis (hematopoietic neoplasm) and sarcomas.…”
Section: Early Days Of Mycmentioning
confidence: 99%